Herbicide Diuron as endocrine disrupting chemicals (EDCs) through histopathalogical analysis in gonads of Javanese medaka (Oryzias javanicus, Bleeker 1854) - Kamarudin, Nur Amiera; Zulkifli, Syaizwan Zahmir; Azmai, Mohammad Noor Amal; Abdul Aziz, Fatin Zahidah; Ismail, Ahmad (MDPI, 2020)
The expeditious augmentation of the agriculture industry is leaving a significant negative impact on aquatic ecosystems. However, the awareness of the impacts of herbicide Diuron toxicities on the non-targeted aquatic organism, especially fish is still lacking. Javanese medaka, a new model fish species were exposed under sublethal levels and the long-term effects on gonads were investigated via histological studies. A total of 210 sexually mature fish were exposed to Diuron at seven different concentrations; control, solvent control, 1, 50, 100, 500, and 1000 μg/L for 21 days. In this study, Diuron caused histopathological alterations in gonads (ovary and testis) of Javanese medaka (Oryzias javanicus) by decreasing in gonadal staging and maturity of germ cells in oogenesis and spermatogenesis of female and male Javanese medaka. The results obtained in this study had proven our hypothesis that long-term exposure of herbicide Diuron can cause alterations in the gonadal histology of the adults of Javanese medaka.